A Corpus-Based Multidimensional Analysis of Pakistan’s Diplomatic Discourse on the Belt and Road Initiative - Zehra, Syedah Nobia; Khan, Mamona Yasmin; Afzaal, Muhammad (Pakistan Languages and Humanities Review, 2025)
The present study examines the linguistic characteristics of diplomatic discourse pertaining to BRI (Belt and Road Initiative) and the CPEC (China-Pakistan Economic Corridor) within Pakistani diplomacy. Seeking to inquire into linguistic patterns as well as communicative functions embedded in the selected diplomatic discourses, the study is underpinned by the analytical lens of Biber’s (1988) multidimensional framework. Its aim is to investigate these discourses using a self-compiled specialized corpus made up of press releases issued by the MOFA (Ministry of Foreign Affairs of Pakistan) from 2013 to 2023. The findings reveal that the selected texts tended to be formal, abstract, informationally dense, impersonal, non-narrative and strategically persuasive. Such characteristics reflect the communicative objectives of diplomatic discourses which lay emphasis on clear, strategically intentional and positively representative communication, carefully designed to promote bilateral cooperation with China and to foster optimism regarding BRI and CPEC. Further, these discourses reflect Pakistan’s steadfastness in completing and advancing CPEC on time. At a broader level, the study highlights the need to probe diplomatic discourses so as to map the underlying functions and strategic deployment of language in international relations.